Cover Feature: The Surface Potential of Zero Charge Controls the Kinetics of Diazonium Salts Electropolymerization (ChemElectroChem 17/2022). Issue 17 (1st August 2022) - Li, Tiexin; Ciampi, Simone; Darwish, Nadim
Abstract : The Cover Feature shows diazonium salt molecules electrostatically adsorbing on a gold surface. More information can be found in the Research Article by T. Li et al .